Serum Lipids Alterations in Patients Under Systemic JAK Inhibitors Treatments in Dermatology: Clinical Aspects and Management - Giovanni Paolino; Mario Valenti; Andrea Carugno; Matteo Bianco; Dario Didona; Matteo Riccardo Di Nicola; Pier Luigi Acutis; Carmen Cantisani; Vittoria Giulia Bianchi; Nicola Zerbinati; Alessandra Narcisi; Antonio Costanzo; et al. (Medicina)
Background and Objectives: Janus kinase inhibitors (JAKi) have significantly advanced the treatment of various dermatological conditions by modulating the JAK-STAT signalling pathway. While these inhibitors have proven effective, they also pose challenges due to associated increase in serum lipid levels and relative potential cardiovascular risks. This perspective work aims to discuss the implications of these lipid alterations proposing management strategies for patients with dermatological disorders under JAKi treatments. Materials and Methods: This manuscript reviews existing and recent literature on the metabolic effects of JAKi, particularly focusing on their impact on lipid profiles in patients treated for dermatological diseases. Results: JAK inhibitors are consistently associated with an increase in both LDL and HDL levels shortly after treatment initiation, which tend to stabilise over time. Despite these changes, there is no clear evidence linking these alterations to an increased risk of major adverse cardiovascular events (MACE), indicating a complex interaction between lipid metabolism and JAK-STAT signalling. Conclusions: Although JAKi may induce lipid changes in patients, raising concerns, especially in ones with existing cardiovascular risks, currently there is no proven link to increased MACE in this population. Monitoring lipid levels, alongside lifestyle modifications and possible statin use, can manage these effects without the need to stopping treatment.